Antibacterial effect and mechanism of anthocyanin from Lycium ruthenicum Murr - Dong, Yuhe; Yang, Chunmiao; Zhong, Wenting; Shu, Yan; Zhang, Yongze; Yang, Dongsheng (Frontiers in Microbiology, 2022)
The inhibitory effects of the anthocyanin obtained from Lycium ruthenicum Murr were tested against several food-borne pathogens were evaluated, such as Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), Aspergillus niger and Penicillium sp. In general, anthocyanin had different antibacterial effect on different bacteri, and the best antibacterial effect on S. aureus, with minimal inhibitory concentration (MIC) of 3.125 mg/mL. Anthocyanin increased the surface hydrophobicity of S. aureus, discharged the intracellular K+, and reduced the total soluble protein, affecting protein synthesis. Fluorescent inverted microscope and flow cytometry (FCM) found a significant increase in fluorescence intensity and lethality relative to the control group, and the dead P3 region to 77.21%. The above suggested a correlation between the antibacterial mechanism of anthocyanin and cell membrane permeability integrity. Biofilm formation was evaluated by the crystal violet assay (CV), silver staining method and methyl thiazolyl tetrazolium (MTT). Scanning electron microscopy (SEM) showed that anthocyanins could change the structure of biofilm.